The great invention : the story of GDP and the making and unmaking of the modern world - Masood, Ehsan (New York : Pegasus Books, 2016)
'The fascinating story of one of the twentieth-century's most influential and dangerously addictive ideas, told through the lives of those who invented it,'--Amazon.com.
Lost history -- The great invention -- GDP and its discontents -- The fight for the formula -- Made in Cambridge -- The Karachi economic miracle -- The talented Mr. Strong --'As vulgar as GDP' -- Exporting Shangri-La -- $33 trillion man -- Stern lessons --'Nothing is more destructive of democracy' -- Unfinished revolution.
Includes bibliographical references (pages 183-226) and index.
Keywords: Gross domestic product -- History; Economics; Economic history